Parameter Genetik dan Deteksi Segregan Transgresif pada Populasi Kacang Tanah (Arachis hypogaea L.) Generasi F3 - Nurhidayah, Siti; Wahyu, Yudiwanti; Bayuardi Suwarno, dan Willy (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
ABSTRACTSelection of transgressive segregants is considered as one effective way of obtaining peanut genotypes with high yield on early segregation. The objective of the study was to estimate genetic parameters and to identify transgressive segregants of peanut family in F3 generation. The experiment was conducted at Leuwikopo, Dramaga, Bogor on August-Desember 2014. The genetic materials evaluated were 218 family F3 generation from 5 biparental population (Jerapah/GWS79A1, GWS79A1/Zebra, GWS79A1/Jerapah, Zebra/GWS79A1 and Zebra/GWS18) and 4 commercial varieties as checks (Gajah, Jerapah, Sima, and Zebra). The experiment was conducted in an augmented randomized complete block design with 4 replications for the checks. The results showed that quantitative characters had continuous distribution and they were controlled by many genes with additive, dominance, complementary epistasis, or additive epistasis gene action. Total number of pod and number of pod had high heritability and moderate genetic coefficient of variation. Selection with 10% intensity showed that 22 families had large total number of pods while six families had larger total number of pods than both parents. Family U2-39 estimated was identified as a putative transgressive segregant with high total number of pod and had smaller variance within family than Sima variety. Keywords: additive,gene action, heritability, GCV